Glutamatergic and dopaminergic modulation of cortico-striatal circuits probed by dynamic calcium imaging of networks reconstructed in microfluidic chips. Issue 1 (December 2018) - Lassus, Benjamin; Naudé, Jérémie; Faure, Philippe; Guedin, Denis; Von Boxberg, Ysander; Mannoury la Cour, Clotilde; Millan, Mark; Peyrin, Jean-Michel
Abstract Although the prefrontal cortex and basal ganglia are functionally interconnected by parallel loops, cellular substrates underlying their interaction remain poorly understood. One novel approach for addressing this issue is microfluidics, a methodology which recapitulates several intrinsic and synaptic properties of cortico-subcortical networks. We developed a microfluidic device where cortical neurons projected onto striatal neurons in a separate compartment. We exploited real-time (low-resolution/high-output) calcium imaging to register network dynamics and characterize the response to glutamatergic and dopaminergic agents. Reconstructed cortico-striatal networks revealed the progressive appearance of cortical VGLUT1 clusters on striatal dendrites, correlating with the emergence of spontaneous and synchronous glutamatergic responses of striatal neurons to concurrent cortical stimulation. Striatal exposure to the NMDA receptor GluN2A subunit antagonist TCN201 did not affect network rhythm, whereas the GluN2B subunit antagonist RO256981 significantly decreased striatal activity. Dopamine application or the D2/D3 receptor agonist, quinpirole, decreased cortico-striatal synchrony whereas the D1 receptor agonist, SKF38393, was ineffective. These data show that cortico-striatal networks reconstructed in a microfluidic environment are synchronized and present characteristics close to those of theirin situ counterparts. They should prove instructive for deciphering the molecular substrates of CNS disorders and evaluating the actions of novel therapeutic agents.